2022
DOI: 10.1111/1747-0080.12727
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of gender dysphoria in eating disorders among gender diverse individuals

Abstract: Aim: Eating concerns, disordered eating and eating disorders have been noted to negatively impact the health and wellbeing of sexual and gender diverse individuals. The aim of this study was to explore the experiences of gender diverse Canadians accessing treatment for eating disorders or disordered eating concerns to gain a deeper understanding of how dietitians and other health providers can provide gender affirming care. Methods: Seven self-identifying gender diverse participants were recruited and took par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Moreover, evidence suggests that ED clinicians are ill-equipped to support gender diverse clients and patients [ 86 ]. Gender diverse individuals have reported significant negative treatment effects related to gender dysphoria [ 81 ].…”
Section: Systemic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, evidence suggests that ED clinicians are ill-equipped to support gender diverse clients and patients [ 86 ]. Gender diverse individuals have reported significant negative treatment effects related to gender dysphoria [ 81 ].…”
Section: Systemic Factorsmentioning
confidence: 99%
“…First, there are several barriers to accessing ED treatment related to cisnormativity. Intake and assessment processes may presume a binary gender identity, and some treatment beds are allocated by gender [ 81 ]. Gender diverse individuals may therefore, be deterred from even seeking treatment.…”
Section: Systemic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Further, a systematic review found the therapeutic relationship between client and dietitian is a valued and multifactorial component of clinical dietetic practice. 40 Studies also explored associations between nutritional status and caregiver burden in Alzheimer's Disease, 41 the influence of the COVID-19 pandemic on body image in LGBTQ+ individuals, 42 the prevalence of food insecurity among community-dwelling individuals with severe mental illness, 17 the influence of gender dysphoria in eating disorders among gender diverse individuals, 43 nutritional intake and food service satisfaction of adults in specialist inpatient mental health services, 18 and the issue of disordered eating among nutrition and dietetic students. 44 This issue of Nutrition & Dietetics allows for opportunities to upskill in mental health through increasing awareness of the realities and implications of good nutrition.…”
mentioning
confidence: 99%
“…Blackstone et al [12] and Simpson et al [125] both found that commercial fitness wearables can negatively affect the user's emotional and physical health by inadvertently promoting behaviours linked to eating disorders such as calorie counting and compensatory behaviours for fitness goals. This is particularly relevant for a group like the queer community as eating disorders have been observed to disproportionately affect queer individuals, especially queer women and gender-diverse individuals [71,94]. The queer community has also shared concerns about the negative mental health impacts wearables might pose when increasing a sense of over-connection between the user and their other devices.…”
Section: Safetymentioning
confidence: 99%